Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd005228.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing neuropathy caused by cisplatin and related compounds

Abstract: Background-Cisplatin and several related antineoplastic agents used to treat many types of solid tumors are neurotoxic, and most patients completing a full course of cisplatin chemotherapy develop a clinically detectable sensory neuropathy. Effective neuroprotective therapies have been sought. Objectives-To examine the efficacy of purported chemoprotective agents to prevent or limit the neurotoxicity of cisplatin and related agents. Search methods-We searched the Cochrane Neuromuscular Disease Group Specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Noteworthy, so far no drug or nutritional supplement has been shown to be capable of preventing or limiting chemotherapy-induced neuropathy, highlighting the relevance to opportunely detect and treat this complication in children with leukemia (11). To our knowledge, there is no previous report on the frequency and type of CIPN in Mexican children with ALL.…”
Section: Introductionmentioning
confidence: 93%
“…Noteworthy, so far no drug or nutritional supplement has been shown to be capable of preventing or limiting chemotherapy-induced neuropathy, highlighting the relevance to opportunely detect and treat this complication in children with leukemia (11). To our knowledge, there is no previous report on the frequency and type of CIPN in Mexican children with ALL.…”
Section: Introductionmentioning
confidence: 93%
“…Neuropathic pain resulting from peripheral neuropathy does not respond as well to opioids and may require other management strategies that employ antidepressants or anticonvulsants [51]. Preventative therapies have also been investigated but with questionable success rates.…”
Section: Symptom Managementmentioning
confidence: 99%
“…A 2011 Cochrane review examined the literature on a wide range of chemoprotective agents for cisplatin neurotoxicity, and concluded that no such agent had been identified in a high quality clinical trial [24]. …”
Section: Discussionmentioning
confidence: 99%